A method for evaluating low-temperature-resistant insulating resin
Patent Information
- Application Number
- CN202611116768.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-30
AI Technical Summary
在这些工况中,材料会经历极低温度(如液氮-196°C、液氦-269°C),其分子链段运动被冻结,可能导致材料从韧性态转变为脆性态,引发机械性能丧失、绝缘性能下降、以及与其它封装材料因热收缩不匹配而开裂等问题,最终导致设备绝缘失效
1、本发明所提供的一种评价耐低温绝缘树脂的方法,结合耐低温绝缘树脂在液氮(-196℃)-室温循环极端工况下的多场耦合、性能非同步衰减、内外关联演化特征,摒弃传统单一参数独立检测、数据简单叠加的评价方式。以材料三大核心性能(电气绝缘性能、热稳定性能、机械力学性能)为基础,引入多参数耦合关联修正系数、非同步老化偏差系数,量化内部热氧老化、微观裂纹与宏观电/力学性能失效的相互作用,精准捕捉材料早期非同步老化特征,实现低温老化程度的全域、精准量化评估。核心设计逻辑为综合老化损伤度=各维度基础老化损伤加权值×多参数耦合修正系数×非同步老化修正系数,既体现各性能老化的基础贡献,又还原参数间内在物理关联,解决传统评价偏差大、早期老化识别难、无法反映真实低温服役可靠性的问题。
Smart Images

Figure CN123017284A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for evaluating low-temperature resistant insulating resins, belonging to the field of materials evaluation technology. Background Technology
[0002] Insulating resins are widely used in electrical equipment operating in cryogenic environments, such as superconducting magnets, aerospace vehicles, polar research stations, and liquefied natural gas facilities. In these conditions, the materials experience extremely low temperatures (such as liquid nitrogen -196°C and liquid helium -269°C), freezing the movement of their molecular chains. This can cause the material to transition from a ductile state to a brittle state, leading to loss of mechanical properties, decreased insulation performance, and cracking due to thermal shrinkage mismatch with other encapsulation materials, ultimately resulting in insulation failure of the equipment.
[0003] Current methods for evaluating low-temperature resistant insulating resins typically focus on only one or a few performance indicators, and the testing environment differs from actual operating conditions. Existing methods either only test the material's basic electrical properties at low temperatures or only examine changes in its mechanical properties at room temperature after low-temperature cycling, failing to comprehensively reflect the evolution of the material's combined electro-thermal-mechanical properties under sustained low-temperature conditions. This isolated, non-operating-condition-based evaluation approach makes it difficult to accurately predict the long-term reliability and lifespan of insulation systems in extreme low-temperature environments.
[0004] Insulation materials for generator stator bars need to meet conditions such as high electrical strength, low dielectric loss, high mechanical strength and toughness, good low temperature resistance and thermal conductivity. However, existing insulation materials are difficult to meet both good low temperature resistance and electrical performance when facing the special low temperature environment, thus failing to meet the special operating conditions of the motor. Summary of the Invention
[0005] The purpose of this invention is to address the aforementioned problems by providing a method for evaluating low-temperature resistant insulating resins. This method allows for a comprehensive evaluation of the thermal, electrical, and mechanical properties of the insulating resin under sustained low-temperature conditions. This is of great significance for accurately evaluating the low-temperature resistance of insulating resins, understanding their reliability in electrical equipment, and preventing related safety accidents.
[0006] The technical solution adopted in this invention is as follows: A method for evaluating and screening low-temperature resistant insulating resins includes a low-temperature cyclic aging simulation test step A, a comprehensive aging damage quantitative assessment model step B, and a comprehensive aging damage quantitative assessment step C. The low-temperature cyclic aging simulation test step A includes: The insulating resin sample was subjected to extreme low temperature placement-room temperature recovery alternating cycle, and the performance parameters of the sample in three dimensions of electrical insulation, thermal stability and mechanical properties were collected simultaneously at multiple cycle number nodes. Step B in establishing a comprehensive quantitative assessment model for aging damage includes: B1. Establish a component damage normalization calculation model that includes electrical insulation aging damage degree De, thermal stability aging damage degree Dt, and mechanical aging damage degree Dm. B2. Using the component damage normalization calculation model of B1 and introducing the weight coefficient w, multi-parameter coupling correction coefficient α, and asynchronous aging correction coefficient β, a comprehensive aging damage degree D assessment model is constructed. The comprehensive aging damage quantitative assessment step C includes: Substitute the performance parameters from step A into the evaluation model from step B to complete the performance evaluation of the low-temperature resistant insulating resin.
[0007] Available for selection The extreme low temperature placement-room temperature recovery alternating cycle single-cycle process is as follows: immerse in liquid nitrogen at -196℃ for 2 hours, remove and let stand at room temperature for 2 hours, with a total number of cycles not less than 60, and a sampling test node is set every 10 cycles.
[0008] The available comprehensive aging damage assessment model is as follows:
[0009] In the formula, D : Comprehensive aging damage degree, dimensionless, with a value range of 0~1. The larger the value, the higher the degree of material aging and the greater the risk of performance failure. De Electrical insulation aging damage degree; Dt Thermal stability aging damage degree; Dm Mechanical aging damage degree; These are the weighting coefficients for electrical insulation, thermal stability, and mechanical properties, respectively, satisfying... ; α : Multi-parameter coupling correction coefficient, used to quantify the intensified coupling effect between internal thermal aging and surface / electrical aging; β : Asynchronous aging correction factor, used to identify latent aging characteristics where surface properties and internal properties evolve asynchronously.
[0010] Available for selection > > .
[0011] Alternatively, the multi-parameter coupling correction coefficient α can be calculated using the following formula:
[0012] in: The coupling sensitivity coefficient; This is a deviation related to both internal and external aging.
[0013] Alternatively, the asynchronous aging correction coefficient β can be calculated as follows:
[0014] In the formula: The value represents the average of the three-dimensional basic aging damage, and the square root term represents the standard deviation of the three-dimensional aging data.
[0015] Alternatively, the electrical insulation performance parameters may include breakdown field strength, insulation resistance, dielectric constant at 50 Hz power frequency, and dielectric loss factor at 50 Hz power frequency. Electrical insulation aging damage :
[0016] 、 These represent the initial and post-cycle breakdown field strengths of the material, respectively. , These are the initial and post-cycle insulation resistances, respectively. , These are the initial and post-cycle dielectric constants, respectively. , These represent the initial dielectric loss and the dielectric loss after cycling, respectively.
[0017] Alternatively, the thermal stability performance parameters may include initial thermal decomposition temperature, glass transition temperature, and thermal weight loss rate. Thermal stability aging damage :
[0018] , These are the initial and post-cycle thermal decomposition temperatures, respectively. , These are the initial and post-cycle glass transition temperatures, respectively. , These represent the initial and post-cycle thermogravimetric rates, respectively.
[0019] Alternatively, the mechanical performance parameters may include bending strength and tensile strength; Mechanical aging damage :
[0020] , These are the initial and aging bending strengths, respectively. , These represent the initial tensile strength and the tensile strength after aging, respectively.
[0021] Alternatively, step A may also include obtaining microscopic morphology data through scanning electron microscopy (SEM) to assist in verifying the evolution of internal microcracks and interface peeling defects in resin samples after alternating low-temperature cycling, and simultaneously combining the macroscopic appearance morphology of the samples to complete auxiliary verification and screening.
[0022] Alternatively, step C may also include classifying the material aging state based on the comprehensive aging damage degree D, to adapt to engineering life assessment and equipment operation and maintenance: 0≤D<0.2: No aging / slight aging, material properties are intact, and the remaining lifespan is sufficient; 0.2≤D<0.4: Mild synchronous aging, slight performance degradation, no operational risk; 0.4≤D<0.6: Moderate aging, with slight potential for asynchronous aging, requiring regular monitoring; 0.6≤D<0.8: Severe asynchronous aging, high risk of latent failure, requires early prediction and replacement; 0.8≤D≤1.0: Complete aging failure, loss of insulation function.
[0023] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. This invention provides a method for evaluating low-temperature resistant insulating resins. It combines the multi-field coupling, asynchronous performance degradation, and internal / external correlation evolution characteristics of low-temperature resistant insulating resins under extreme conditions of liquid nitrogen (-196℃) to room temperature cycling, abandoning the traditional evaluation method of independent detection of single parameters and simple data aggregation. Based on the three core properties of the material (electrical insulation performance, thermal stability performance, and mechanical properties), it introduces multi-parameter coupling correlation correction coefficients and asynchronous aging deviation coefficients to quantify the interaction between internal thermo-oxidative aging, microcracks, and macroscopic electrical / mechanical performance failure. This accurately captures the early asynchronous aging characteristics of the material, achieving a comprehensive and accurate quantitative assessment of the degree of low-temperature aging. The core design logic is: Comprehensive aging damage degree = weighted value of basic aging damage in each dimension × multi-parameter coupling correction coefficient × asynchronous aging correction coefficient. This not only reflects the basic contribution of each performance aging but also restores the inherent physical correlation between parameters, solving the problems of large deviations in traditional evaluations, difficulty in identifying early aging, and inability to reflect the true reliability of low-temperature service.
[0024] 2. The method for evaluating low-temperature resistant insulating resin provided by this invention involves simultaneously measuring multiple key parameters of the insulating resin under different cycles in liquid nitrogen, such as electrical properties (e.g., breakdown field strength, dielectric constant, insulation resistance, dielectric loss), thermal properties (e.g., thermogravimetric loss, initial decomposition temperature, glass transition temperature), mechanical properties (e.g., flexural strength, tensile strength), and microstructure (SEM). This systematic and comprehensive evaluation breaks through the limitations of traditional single-index evaluation and achieves a comprehensive evaluation of the material's low-temperature resistance performance. Attached Figure Description
[0025] Figure 1 It is the breakdown field strength of JF-9821 resin after different cycles.
[0026] Figure 2 It is the flexural strength of JF-9821 resin after different cycles.
[0027] Figure 3 It is the tensile strength of JF-9821 resin after different cycles.
[0028] Figure 4 These are the initial thermal decomposition temperatures of JF-9821 resin after different cycles.
[0029] Figure 5 It is the insulation resistance of JF-9821 resin after different cycles.
[0030] Figure 6 This is a graph showing the thermal conductivity of JF-9821 resin after different cycles.
[0031] Figure 7 This is a graph showing the dielectric constant of JF-9821 resin after different cycles.
[0032] Figure 8 This is a graph showing the dielectric loss of JF-9821 resin after different cycles.
[0033] Figure 9 It refers to the glass transition temperature of JF-9821 resin after different cycles. Detailed Implementation
[0034] The present invention will now be described in detail with reference to the accompanying drawings.
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0036] Example A method for evaluating low-temperature resistant insulating resins, using JF-9821 low-temperature resistant insulating resin as the research object, involves immersing the JF-9821 resin in liquid nitrogen for 2 hours, then removing it and keeping it at room temperature for 2 hours as one cycle, for a total of 60 cycles, with testing performed every 10 cycles, and the method of the present invention used for evaluation.
[0037] Low-temperature cyclic aging simulation test step A: Breakdown field strength test: The test is conducted according to standard GB / T1408.1-2006 (IEC60243-1:1998). Sample size is 40×40×0.5mm. Three samples are prepared for testing. The sample is placed between the electrodes and immersed in insulating oil. Voltage is then increased until the sample breaks down. The voltage increase rate is 1kV / s. The breakdown field strength is obtained by the ratio of the breakdown voltage to the breakdown point thickness, and the average field strength of the three samples is taken as the breakdown field strength of this type of sample.
[0038] The breakdown field strength of the resin remained relatively stable at 10, 20, and 30 cycles. This is because if initial defects (such as micropores or cracks) exist within the resin, low-temperature shrinkage may temporarily close some of these defects, delaying the formation of breakdown channels. This results in a slow decrease in the breakdown field strength. However, as the number of cycles increases, the breakdown field strength gradually decreases, but at a slower rate. This is because repeated thermal expansion and contraction lead to the formation of microcracks within the resin, increasing defect density and charge mobility. At low temperatures, molecular chain segment movement is hindered, enhancing partial discharge activity and accelerating material aging.
[0039] Dielectric constant testing: A broadband dielectric spectrum / thermal stimulation current testing system, model GmbH, was used. The testing was conducted according to standard GB / T1409-2006. The changes in dielectric constant and dielectric loss with frequency were obtained, and six samples were prepared for testing. Dielectric constant at 50Hz (power frequency): JF-9821 resin: 6.9630; after 60 cycles: 15.4979, with a change rate of 123%. Dielectric loss at 50Hz (power frequency): JF-9821 resin: 0.0785; after 60 cycles: 0.2294.
[0040] Insulation resistance test: Referring to standard QJ2220.2-1992, a Megger IDAX300 meter was used at 18℃ and 50% relative humidity, with an electrode distance of 30mm and a measurement voltage of 200V. Three samples were prepared for testing, and the average value was taken. After 30 cycles, the insulation resistance of JF-9821 resin decreased significantly, indicating severe damage to the internal structure of the material and complete interface peeling. At this point, the material could no longer meet the insulation requirements.
[0041] Dielectric loss test: Six samples were prepared for testing using a broadband dielectric spectroscopy / thermal-stimulated current testing system, model GmbH. The samples were placed in the measuring chamber of the tester, ensuring good contact between the samples and the measuring electrodes. The test frequency and voltage were set. The current of the samples under AC voltage was measured, and the dielectric loss factor (tanδ) was calculated.
[0042] Scanning electron microscopy (SEM) testing: Observing the surface morphology and microstructure of the material. After being cycled in liquid nitrogen for different numbers of times, the microstructure of JF-9821 resin remained essentially unchanged.
[0043] Flexural strength test: A flexural test was conducted on the composite material using the Sansi Measurement and Control System. Parameters such as the fracture flexural strength of the composite structure were determined according to the national standard GB / T9341-2008 "Determination of Flexural Properties of Plastics". Five samples were prepared for testing. After 10 cycles, the flexural strength of the resin decreased significantly. It remained stable after 20 and 30 cycles, but decreased further with increasing cycle count. This is because oxygen may accelerate the oxidative degradation of the resin during the room temperature recovery phase, reducing flexural strength.
[0044] Bending strength calculation formula:
[0045] In the formula, F is the applied force, in Newtons. b and h are the width and thickness of the sample, respectively.
[0046] Tensile strength test: This test determines the maximum load-bearing capacity of a material under tensile load, reflecting the material's ductility and toughness. After 10 cycles, the tensile strength increases significantly; thereafter, as the number of cycles continues to increase, the tensile strength increases slowly.
[0047] Thermogravimetric analysis (TGA): This test measures the mass change of a material during heating to determine its thermal stability and decomposition temperature. After 10 cycles, the weight loss rate decreased slightly. With increasing cycle count, the weight loss rate tended to stabilize. The initial thermal decomposition temperature indicates that JF-9821 resin has good thermal stability.
[0048] Differential scanning calorimetry (DSC): During the initial cycles, the glass transition temperature (Tg) of the JF-9821 resin sample increased slightly. This may be because the extreme low temperature of liquid nitrogen immersion (-196℃) may induce a post-curing reaction in the JF-9821 resin matrix (further crosslinking of the incompletely cured portion), resulting in a slight increase in Tg. After 50 and 60 cycles, Tg tended to stabilize.
[0049] Dynamic thermomechanical analysis (DMA): The storage modulus of JF-9821 resin decreased with increasing temperature after different cycling cycles, showing a significant decrease within a certain temperature range, and eventually approaching zero. At lower temperatures, JF-9821 resin is in a glassy state, with frozen molecular chains and low mobility, resulting in a higher storage modulus. As the temperature increases, molecular chain segments gain some freedom, causing the storage modulus to decrease. Near the glass transition temperature (Tg), the storage modulus decreases significantly, indicating a transition from a glassy to a rubbery state. Above Tg, molecular chain segments have greater freedom of movement, and the storage modulus continues to decrease, but at a slower rate. The loss tangent initially increases with temperature, peaks near Tg, and then decreases sharply. The tanδ peak remains a single peak throughout the cycling process, demonstrating that no phase separation occurred in the epoxy curing products within the composite material after 60 cycles. 116HU resin completely crumbled after only 2 hours of immersion in liquid nitrogen, indicating very poor low-temperature resistance.
[0050] Test results are as follows Figures 1-9 As shown.
[0051] Step B in establishing a comprehensive quantitative assessment model for aging damage: 1. Comprehensive Aging Damage Assessment Model
[0052] In the formula: D : Comprehensive aging damage degree, dimensionless, with a value range of 0~1. The larger the value, the higher the degree of material aging and the greater the risk of performance failure. De Electrical insulation aging damage degree; Dt Thermal stability aging damage degree; Dm Mechanical aging damage degree; These are the weighting coefficients for electrical, thermal, and mechanical properties, respectively, satisfying... ; α : Multi-parameter coupling correction coefficient, used to quantify the intensified coupling effect between internal thermal aging and surface / electrical aging; β : Asynchronous aging correction factor, used to identify latent aging characteristics where surface properties and internal properties evolve asynchronously.
[0053] 2. Calculation of basic aging damage degree for each item The three core dimensions of basic aging damage are all calculated using initial performance benchmark normalization to eliminate differences in parameter dimensions: (1) Degree of electrical insulation aging damage :
[0054] 、 These represent the initial and post-cycle breakdown field strengths of the material, respectively. , These are the initial and post-cycle insulation resistances, respectively. , These are the initial and post-cycle dielectric constants, respectively. , These represent the initial dielectric loss and the dielectric loss after cycling, respectively.
[0055] (2) Thermal stability aging damage :
[0056] , These are the initial and post-cycle thermal decomposition temperatures, respectively. , These are the initial and post-cycle glass transition temperatures, respectively. , These represent the initial and post-cycle thermogravimetric rates, respectively.
[0057] (3) Mechanical aging damage degree :
[0058] , These are the initial and aging bending strengths, respectively. , These represent the initial tensile strength and the tensile strength after aging, respectively.
[0059] 3. Weighting coefficients Electrical safety > thermal stability > mechanical properties. Electrical properties determine whether equipment will fail instantaneously, thermal stability determines the root cause of material aging, and mechanical properties provide auxiliary structural protection. Therefore, the order is: .
[0060] 4. Multi-parameter coupling correction coefficient
[0061] in: The coupling sensitivity coefficient is uniformly set to 0.8 for electrical insulation materials; This represents the deviation between internal and external aging; the larger the value, the stronger the parameter coupling effect and the more significant the cumulative damage from aging. Value range: When there is no coupling deviation The coefficient increases as coupling aging intensifies.
[0062] 5. Asynchronous aging correction factor
[0063] The core innovation coefficient of the formula is specifically designed to identify asynchronous aging characteristics mentioned in the text (surface qualified but internally deteriorated, internally intact but surface collapsed), solving the problems of missed early aging and lifespan prediction errors.
[0064] To eliminate errors from manual experience-based value selection and achieve full-parameter quantitative calculation, a quantitative formula for the asynchronous aging correction coefficient β is constructed based on multi-dimensional aging deviation entropy values. This formula accurately characterizes the degree of imbalance in aging across three dimensions: mechanical properties, electrical insulation, and thermal stability. The judgment logic and calculation formula are as follows:
[0065] In the formula: The average value of the three-dimensional basic aging damage is given by the square root term, which represents the standard deviation of the three-dimensional aging data. This accurately reflects the discrete deviation of the aging degree in each dimension and perfectly matches the asynchronous aging characteristics of materials.
[0066] Coefficient value determination mechanism: During synchronous aging, the three-dimensional aging values are basically consistent, and the standard deviation approaches 0. The greater the aging asynchrony, the larger the standard deviation. β The numerical values increase synchronously, automatically amplifying the weight of latent aging damage, eliminating the need for manual grading and judgment, and achieving fully automated quantitative calculation.
[0067] 6. Quantitative Judgment Standards for Aging Levels Based on the comprehensive aging damage degree D, the aging state of materials is classified to adapt to engineering life assessment and equipment operation and maintenance: (1) 0≤D<0.2: No aging / slight aging, material properties are intact, and the remaining lifespan is sufficient; (2) 0.2≤D<0.4: Mild synchronous aging, slight performance degradation, no operational risk; (3) 0.4≤D<0.6: Moderate aging, with slight potential for asynchronous aging, requiring regular monitoring; (4) 0.6≤D<0.8: Severe asynchronous aging, high risk of latent failure, requires early prediction and replacement; (5) 0.8≤D≤1.0: Complete aging failure, loss of insulation function.
[0068] Comprehensive aging damage quantitative assessment step C: The aging status of JF-9821 resin was evaluated using the method of this invention after 60 cycles of testing. The calculation process is as follows.
[0069] ① Electrical insulation aging damage De =1 1 / 4(20.016 / 29.482+28.3 / 747+6.9630 / 15.4979+0.0785 / 0.2294)=0.547 ② Thermal stability aging damage Dt =1 - 1 / 3(268.3 / 315.5 + 32.22 / 55.10 + 5.0452 / 3.2598) = 0.219 ③ Mechanical aging damage degree Dm =1–1 / 2(32.502 / 80.228+8.990 / 35.051)=0.605 ④ Basis-weighted aging damage: 0.45×0.547 + 0.35×0.219 + 0.20×0.605 = 0.431 ⑤ Multi-parameter coupling correction coefficient α = 1 + 0.8 × |0.219 – √(0.547 × 0.605)| = 1.207 ⑥ Asynchronous aging correction factor Da =0.457, β=1.194 ⑦ Overall aging damage D =1.207 × 0.431 × 1.194 = 0.623 D=0.623 indicates severe asynchronous aging. After 60 liquid nitrogen cycles, the material showed significant risks of low-temperature brittleness and insulation degradation, which is completely consistent with the experimental results.
[0070] This invention provides a highly efficient, accurate, and industrially applicable method for evaluating and screening low-temperature resistant insulating resins for generators. This method can accurately evaluate the low-temperature resistance of insulating resins, understand their reliability in electrical equipment, and prevent related safety accidents. By integrating multi-dimensional performance test data, this invention achieves cross-validation between different parameters, thereby enhancing the overall credibility and scientific basis of the evaluation conclusions. This application innovatively designs an accelerated cycling experiment of "liquid nitrogen immersion-room temperature recovery," successfully obtaining performance evolution curves by systematically sampling and testing at multiple time points at different cycle periods (e.g., 10 / 20 / 30 cycles). This not only enables dynamic tracking of the performance degradation law of materials under alternating low-temperature stress, but more importantly, it can accurately quantify the cumulative damage effect, thus significantly improving the realism of the operating condition simulation of the testing method and providing key technical support for accurately predicting the service life and durability of materials in low-temperature environments.
[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. The invention extends to any new features or combinations disclosed in this specification, and any modifications, equivalent substitutions, and improvements made within the spirit and principles of the invention should be included within the scope of protection of the invention. It will be apparent to those skilled in the art that the invention is not limited to the details of the above exemplary embodiments.
Claims
1. A method for evaluating low-temperature resistant insulating resins, characterized in that: The process includes step A, low-temperature cycling aging simulation testing; step B, establishing a comprehensive aging damage quantitative assessment model; and step C, comprehensive aging damage quantitative assessment. The low-temperature cyclic aging simulation test step A includes: The insulating resin sample was subjected to extreme low temperature placement-room temperature recovery alternating cycle, and the performance parameters of the sample in three dimensions of electrical insulation, thermal stability and mechanical properties were collected simultaneously at multiple cycle number nodes. Step B in establishing a comprehensive quantitative assessment model for aging damage includes: B1. Establish a component damage normalization calculation model that includes electrical insulation aging damage degree De, thermal stability aging damage degree Dt, and mechanical aging damage degree Dm. B2. Using the component damage normalization calculation model of B1 and introducing the weight coefficient w, multi-parameter coupling correction coefficient α, and asynchronous aging correction coefficient β, a comprehensive aging damage degree D assessment model is constructed. The comprehensive aging damage quantitative assessment step C includes: Substitute the performance parameters from step A into the evaluation model from step B to complete the performance evaluation of the low-temperature resistant insulating resin.
2. The method as described in claim 1, characterized in that: The extreme low temperature placement-room temperature recovery alternating cycle single-cycle process is as follows: immerse in liquid nitrogen at -196℃ for 2 hours, remove and let stand at room temperature for 2 hours, with a total number of cycles not less than 60, and a sampling test node is set every 10 cycles.
3. The method as described in claim 1, characterized in that: The comprehensive aging damage assessment model is as follows: In the formula, D : Comprehensive aging damage degree, dimensionless, with a value range of 0~1. The larger the value, the higher the degree of material aging and the greater the risk of performance failure. De Electrical insulation aging damage degree; Dt Thermal stability aging damage degree; Dm Mechanical aging damage degree; These are the weighting coefficients for electrical insulation, thermal stability, and mechanical properties, respectively, satisfying... ; α : Multi-parameter coupling correction coefficient, used to quantify the intensified coupling effect between internal thermal aging and surface / electrical aging; β : Asynchronous aging correction factor, used to identify latent aging characteristics where surface properties and internal properties evolve asynchronously.
4. The method as described in claim 3, characterized in that: The formula for calculating the multi-parameter coupling correction coefficient α is as follows: in: The coupling sensitivity coefficient; This is a deviation related to internal and external aging.
5. The method as described in claim 3, characterized in that: The asynchronous aging correction coefficient β is calculated as follows: In the formula: The value represents the average of the three-dimensional basic aging damage, and the square root term represents the standard deviation of the three-dimensional aging data.
6. The method as described in claim 3, characterized in that: The electrical insulation performance parameters include breakdown field strength, insulation resistance, dielectric constant at 50 Hz power frequency, and dielectric loss factor at 50 Hz power frequency. Electrical insulation aging damage : 、 These represent the initial and post-cycle breakdown field strengths of the material, respectively. , These are the initial and post-cycle insulation resistances, respectively. , These are the initial and post-cycle dielectric constants, respectively. , These represent the initial dielectric loss and the dielectric loss after cycling, respectively.
7. The method as described in claim 3, characterized in that: The thermal stability performance parameters include initial thermal decomposition temperature, glass transition temperature, and thermal weight loss rate. Thermal stability aging damage : , These are the initial and post-cycle thermal decomposition temperatures, respectively. , These are the initial and post-cycle glass transition temperatures, respectively. , These represent the initial and post-cycle thermogravimetric rates, respectively.
8. The method as described in claim 3, characterized in that: The mechanical performance parameters include bending strength and tensile strength. Mechanical aging damage : , These are the initial and aging bending strengths, respectively. , These represent the initial tensile strength and the tensile strength after aging, respectively.
9. The method as described in claim 1, characterized in that: Step A also includes obtaining microscopic morphology data through scanning electron microscopy (SEM) to assist in verifying the evolution of internal microcracks and interface peeling defects in resin samples after alternating low-temperature cycles, and simultaneously combining the macroscopic appearance morphology of the samples to complete auxiliary verification and screening.
10. The method as described in claim 3, characterized in that: Step C also includes classifying the material aging state based on the comprehensive aging damage degree D, adapting it to engineering life assessment and equipment operation and maintenance: 0≤D<0.2: No aging / slight aging, material properties are intact, and the remaining lifespan is sufficient; 0.2≤D<0.4: Mild synchronous aging, slight performance degradation, no operational risk; 0.4≤D<0.6: Moderate aging, with slight potential for asynchronous aging, requiring regular monitoring; 0.6≤D<0.8: Severe asynchronous aging, high risk of latent failure, requires early prediction and replacement; 0.8≤D≤1.0: Complete aging failure, loss of insulation function.
